Thematic Analysis of Technology Use by Urban Couples in Stress Management - Pingkan Cynthia Belinda, Rumondor; Sheilla Lim, Omar Lim; Ross Azura, Zahit; Andre Ferdinand, Julianto; Charoline, Xessa; Khansa Najla, Pramesti; Martinus Fieser, Sitinjak (MDPI, 2024)
Urban couples spend much time working, which poses challenges in their daily life. These challenges can cause stress, affecting relationship quality and an individual’s well-being. We identified and described stressors and explored the use of technology to manage their stress. The participants consisted of three couples living in the Greater Jakarta area. A focus group discussion was used to collect the data, and inductive thematic analysis was used to analyze it. Urban couples experienced relationship stress, parenting stress, financial stress, work-related stress, and daily hassles. Couples can manage stress by using digital media and smart communication technology to provide entertainment and communication, as well as to search for information.